Analisis Framing Pemberitaan “Ndasmu Etik” dalam Debat Calon Presiden (Capres) 2024 Di Portal Kompas.Com dan Tempo.Co - Siti Nur Aisah; Mochammad Mirza; Ari Suseno (Economic Reviews Journal, 2024)
This research is entitled "Analysis of the Framing of Reporting "Ndasmu Etik" in the 2024 Presidential Candidate (Capres) Debate on the Kompas.Com and Tempo.Co Portals". This research aims to find out how the online media Kompas.com and tempo.co frame the reporting of "ndasmu istik" made by Prabowo during the presidential election debate forum. This research uses framing analysis, which analyzes news using syntax, script, thematic and rhetorical. The theory used in this research is framing analysis. The objects of this research are 7 (seven) Kompas.com news texts and 7 (seven) Tempo.co news texts regarding the "ndasmu istik" that Prabowo uttered during the debate. This research method uses a descriptive qualitative approach. This research uses the Zhongdang Pan and Gerald M Koscicki model analysis technique. The results of the research show that the news published by the online media kompas.com attempts to lead public opinion towards Prabowo's behavior and remarks which are considered inappropriate, while the online media Tempo.co has its own way of framing news.